2018
DOI: 10.1371/journal.pone.0204828
|View full text |Cite
|
Sign up to set email alerts
|

Harman and norharman, metabolites of entomopathogenic fungus Conidiobolus coronatus (Entomopthorales), disorganize development of Galleria mellonella (Lepidoptera) and affect serotonin-regulating enzymes

Abstract: Naturally occurring entomopathogenic fungi such as Conidiobolus coronatus are important regulatory factors of insect populations. GC-MS analysis of fungal cell-free filtrates showed that C. coronatus synthesizes two β- carboline alkaloids: harman and norharman. Significantly higher levels of both alkaloids are produced by C. coronatus in minimal postincubation medium than in rich medium. The beta-carboline alkaloids may have an effect on the nervous system of insects and their behavior. Harman and norharman we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The first evidence that the entomopathogenic fungus C. coronatus produces two toxic β-carboline alkaloids, harman and norharman, was given by Wrońska et al [10]. In this study, the highest amounts of norharman and harman were found in cell-free filtrates of MM (minimal medium) post-incubation medium, and that both alkaloids delayed Galleria mellonella pupation and adult eclosion.…”
Section: Introductionsupporting
confidence: 48%
“…The first evidence that the entomopathogenic fungus C. coronatus produces two toxic β-carboline alkaloids, harman and norharman, was given by Wrońska et al [10]. In this study, the highest amounts of norharman and harman were found in cell-free filtrates of MM (minimal medium) post-incubation medium, and that both alkaloids delayed Galleria mellonella pupation and adult eclosion.…”
Section: Introductionsupporting
confidence: 48%
“…Likewise, psychoactive cannabinoids, well known from Cannabis sativa , have been recently confirmed from liverwort, providing a marked example of convergent evolution of bioactive plant secondary metabolites ( Chicca et al 2018 ). Similarly, β-carboline alkaloids, are found in both plants and fungi, including in the Entomophthoralean fungus, Conidiobolus coronatus , where it is thought to interfere with insect serotonin levels and larval development ( Wrońska et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their ephemeral nature, obligate lifestyle, and large genome size, Entomophthorales with both SD and AHT behaviors have been grossly underrepresented in vitro lab investigations as well as in phylogenetic and phylogenomic studies ( Spatafora et al 2016 ; Gryganskyi et al 2017 ). However, recent genomic, transcriptomic, and metabolomic approaches have further helped elucidate important aspects of SD-inducing entomopathogens ( Grell et al 2011 ; Małagocka et al, 2015 , De Fine Licht et al, 2017 ; Arnesen et al, 2018 ; Elya et al 2018 ; Wrońska et al, 2018 ). Likewise, -omics based investigations of SD-inducing Hypocrealean entomopathogens have helped unravel infection processes and host responses, especially for the “zombie ant fungus” Ophiocordyceps unilateralis ( De Bekker et al 2014 , 2017 ; Fredericksen et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known regarding the metabolic production of members of the Zoopagomycota or the zoosporic lineages. Alkaloid compounds have been described in several members of the Entomophthoromycotina, with different activities in their insect hosts (Claydon, ; Wrońska et al ., ; Boyce et al ., ). However, very little is known regarding the genomic organization of these pathways.…”
Section: Metabolic Complexitymentioning
confidence: 99%